2020
DOI: 10.3390/ijms21010352
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FGFR2-Signaling Attenuates a Homology-Mediated DNA Repair in GIST and Sensitizes Them to DNA-Topoisomerase II Inhibitors

Abstract: Deregulation of receptor tyrosine kinase (RTK)-signaling is frequently observed in many human malignancies, making activated RTKs the promising therapeutic targets. In particular, activated RTK-signaling has a strong impact on tumor resistance to various DNA damaging agents, e.g., ionizing radiation and chemotherapeutic drugs. We showed recently that fibroblast growth factor receptor (FGFR)-signaling might be hyperactivated in imatinib (IM)-resistant gastrointestinal stromal tumors (GIST) and inhibition of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
(58 reference statements)
0
10
0
1
Order By: Relevance
“…The administration of BGJ398 reduced cell viability and enhanced apoptosis in GIST (gastrointestinal stromal tumor) T-1 cell line resistant to imatinib, but not in parental cells [ 46 ]. In GIST cells resistant to doxorubicin, the administration of BGJ398 resulted in a delay in DNA repair [ 212 ]. BGJ398 was also found to reduce cell viability, induce apoptosis, and increase the cytotoxicity of 5-fluorouracil or oxaliplatin in CRC cells [ 52 ].…”
Section: Sensitization Of Tumor Cells To Chemotherapy By Inhibition Of Fgf/fgfr Complex Activitymentioning
confidence: 99%
“…The administration of BGJ398 reduced cell viability and enhanced apoptosis in GIST (gastrointestinal stromal tumor) T-1 cell line resistant to imatinib, but not in parental cells [ 46 ]. In GIST cells resistant to doxorubicin, the administration of BGJ398 resulted in a delay in DNA repair [ 212 ]. BGJ398 was also found to reduce cell viability, induce apoptosis, and increase the cytotoxicity of 5-fluorouracil or oxaliplatin in CRC cells [ 52 ].…”
Section: Sensitization Of Tumor Cells To Chemotherapy By Inhibition Of Fgf/fgfr Complex Activitymentioning
confidence: 99%
“…The FGF2/R2 signaling has been extensively studied in GIST as a drug resistance mechanism. Sergei et al [ 54 ] and Boichuk et al [ 55 ] demonstrated that the blockage of FGFR2 signaling could enhance the responsiveness to DNA-Topoisomerase II inhibitors[ 54 ] while the downregulation of FGF2 signaling might stimulate the response to imatinib[ 55 ]. It’s contribution in GIST progression has been reviewed[ 56 ] but data about potential effects in GIST vascularization process are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the sensitivity of STS and (in less extent) GIST to DNA-damaging agents was shown in multiple reports [20][21][22][23], however, to date, a little is known about the role of AKT in DNA DSB repair (in particular HR) in STS and GIST. Given that inhibition of FGF-signaling in GIST effectively sensitized them to Topo II inhibitors via attenuating HR-mediated DNA DSB repair [35], we sought to examine the downstream signaling pathways responsible for this phenomenon. We present here the novel data illustrating that AKT-but not a MEK-signaling pathway regulates an efficiency of homology-mediated DNA damage repair in STS and GIST.…”
Section: Discussionmentioning
confidence: 99%